Terapia interdisciplinar para obesidade: efeito sobre a relação entre sintomas psicológicos, parâmetros inflamatórios e proteoma plasmático - Carvalho, Lorenza Oliveira Testa [UNIFESP] (2016)
The knowledge about obesity?s etiology is multifactorial and physiological mechanisms that regulate its development are of great importance in the study of this disease, as well as the influence of psychological factors. Researches in obesity study group (GEO) have elucidated the great efficiency of interdisciplinary therapy in reducing the weight and comorbidities associated with interventions 6 or 12 month follow-up. Given the significant incidence and impact of these conditions and the supposed association between them, this study aimed to expand the scientific knowledge about the possible explanatory factors of the symptoms of anxiety and depression in weight loss as well as proteomics grade I and II obesity separately. This research followed 63 obese women group. The volunteers? selection was performed by screening after media advertising (newspaper, radio, internet, posters, etc.) to participate in an interdisciplinary intervention design changes in lifestyle and weight loss, during the years 2012 and 2013 in the city of Santos (SP). These were submitted to nutritional, psychological and exercise guidance. Finally, it was observed that 6 months of obesity interdisciplinary treatment was effective in weight loss, body composition and the inflammatory parameters improvement and reducing depression and anxiety symptoms. In grade I obesity group, the levels of serum VCAM, ICAM, MCP-1 and PAI-1 were identified as predictors of anxiety symptoms after therapy. For depression, only serum levels of VCAM influenced this symptom. Also in this group, the proteomic analysis of plasma suggested changes in the process of digestion and lipids absorption, what could influence the improvement in lipid metabolism and in the control of food intake for this group. In grade II, it was observed that the symptoms of depression were influenced by the MCP-1, although we have not observed significant reduction of this parameter after the interventions. Analysis of plasma suggested a reduction in the activation of complement and coagulation systems at the end of interdisciplinary therapy 6 months. The result of the interdisciplinary therapy confirms the physical and psychological benefits of this model of grades I and II obesity treatment. However, more studies are necessary to investigate the factors associated with psychological symptoms as well as the ways suggested in the plasma proteome analysis in obese women.